One-Pot Synthesis of 1,8-Dioxodecahydroacridines using Ag-TiO2 Nanocomposite as a Mild and Heterogeneous Catalytic System - Masoudi, Ali A.; Vahdat, Seyed Mohammad; Khaksar, Samad (Letters in Organic Chemistry, 2022)
Ag-TiO2 nanocomposite is reported to be an efficient, active, and benign recyclable catalyst for highly efficient synthesis of 1,8-dioxodecahydroacridine derivatives from dimedone, aromatic aldehydes, and several anilines or ammonium acetate in ethanol as a solvent at room temperature in a short reaction time and suitable yield. This catalyst is effortlessly recycled by simple filtration and can be reused up to five times with only a negligible loss in its catalytic effectiveness. Low catalyst loading, cost-effectively mild conditions, non-chromatographic purification of target compounds, excellent atom economy, informal procedure, use of a cheaply accessible nanocomposite catalyst, and recyclability of the catalyst are all significant benefits of this method. AFM analysis is performed to confirm the structure, topography, and morphology of Ag-TiO2 nanocomposite. 1,8-dioxodecahydroacridine derivatives having natural significance possess a wide range of pharmacological activities; for instance, antibacterial, antimalarial, anticancer, and mutagenic properties. In terms of the distinctions between aldehydes and anilines, this approach offers a wide range of applications.
Keywords: 8-dioxodecahydroacridines